Socialization of The Concept of Islamic-Based Umkm Economic Development In Jaruju Laut Village, Tatah Makmur District, Banjar Regency - Sauqi, Muhammad; Malihah, Lola; Rusdiana, Rusdiana (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
This Aricle of Community Service (PKM) is motivated by the existence of Jaruju Laut Village, Tatah Makmur District , which aims to provide socialization about the Islamic-based MSME economic concept, so that the people of Jaruju Laut Village can develop the economy better. The method used in this PKM article is a field study by directly providing socialization to the people of Jaruju Laut Village while the data source is through observation, interviews and documentation. The results of this PKM, first, the people of Jaruju Laut Village understand more about the concept of Islamic-based MSMEs. Second, the people of Jaruju Laut Village can practice entrepreneurial strategies and marketing management in accordance with Islamic concepts.